Identification of Ferroptosis-Related Genes in Patients with Renal Ischemia-Reperfusion Injury - Jiang G; Li J; Dong R; Chen Y; Zhang X; Shi X (International Journal of General Medicine)
Guangwei Jiang,1 Jikuan Li,1 Ruoyu Dong,1 Yuyan Chen,2 Xiaoyu Zhang,1 Xiaoming Shi1 1Department of Vascular Surgery, Hebei General Hospital, Shijiazhuang, Hebei Province, 050000, People’s Republic of China; 2Second Department of Rehabilitation Medicine, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei Province, 050051, People’s Republic of ChinaCorrespondence: Xiaoming Shi, Email shixm2021@outlook.comBackground: During acute kidney injury, hypoxic injury following reactive oxygen species (ROS) production due to reoxidation leads to severe inflammation and ferroptosis. Thus, the aim of the current research was to determine the ferroptosis-related biomarkers in IRI injury.Methods: GSE43974 dataset was analyzed to identify differentially expressed genes (DEGs) using bioinformatics analysis. The intersection of DEGs and ferroptosis-related genes was identified as differentially expressed ferroptosis-related genes (DEFRGs). Finally, a renal ischemia-reperfusion model was made using mice, and the model was identified by HE staining and markers of IRI, including BUN and Scr. Changes in the expression of hub gene in the model and sham groups were detected by RT-pcr.Results: A total of 3950 DEGs were identified between the IRI and control samples. Thereafter, 74 DEFRGs are obtained by taking the intersection of DEGs and ferroptosis-related genes. The GO analysis indicated that DEFRGs were mainly enriched in response to oxidative stress-related pathway. By MCODE, ATF3, ATF4, ATG3, ATG5, BECN1, DDIT3, HSPA5, NFE2L2, WIPI1, XBP1 were identified as hub genes. ATF3, DDIT3, ATF4, and ATG3 with AUC more than 0.7 were identified as biomarkers. It was confirmed by RT-pcr that the expression of hub genes ATF3, DDIT3, ATF4 was significantly elevated, and the expression of ATG3 was significantly reduced in the IRI model group. It was consistent with the expected results of data analysis in GEO.Conclusion: In conclusion, our study identified 4 ferroptosis-related hub genes in the IRI and demonstrated that they are potential diagnostic biomarkers for IRI.Keywords: acute kidney injury, IRI, hub gene, ferroptosis-related genes, ROS